2019
DOI: 10.1080/13685538.2019.1613358
|View full text |Cite
|
Sign up to set email alerts
|

Unusual presentation of epidermoid cyst from testis in an aging male

Abstract: Epidermoid cysts, which constitute 1% of all testicular tumors, are considered to be benign even though histogenesis is not clear. Patients usually suffer from painless scrotal mass or this mass is realized during the routine physical examination. Hematospermia may be a finding for both benign and malignant testicular tumors. Many authors advocate the testicular sparing surgery in the treatment but epidermoid cysts are usually treated with radical inguinal orchiectomy, because of the difficulties in the diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“… 11 Furthermore, differentiating epidermoid cysts from other testicular tumors presents a challenge due to their similar clinical presentation as a non-tender, smooth, palpable mass, emphasizing the necessity for a comprehensive clinical approach to ensure an accurate diagnosis. 1 In addition, certain atypical forms have been described, notably the case of an epidermoid cyst revealed by hematospermia, 12 and two cases of benign tumors mimicking testicular torsion in triorchidism. 13 , 14 …”
Section: Discussionmentioning
confidence: 99%
“… 11 Furthermore, differentiating epidermoid cysts from other testicular tumors presents a challenge due to their similar clinical presentation as a non-tender, smooth, palpable mass, emphasizing the necessity for a comprehensive clinical approach to ensure an accurate diagnosis. 1 In addition, certain atypical forms have been described, notably the case of an epidermoid cyst revealed by hematospermia, 12 and two cases of benign tumors mimicking testicular torsion in triorchidism. 13 , 14 …”
Section: Discussionmentioning
confidence: 99%
“…The histological features of epidermoid cysts have shown that the cysts are usually lined by squamous cells and contain keratin 6. There are usually no teratoma features present in the cyst and they usually have normal tumour markers 7…”
Section: Discussionmentioning
confidence: 99%